Pulsatile Drug Delivery System Triggered by Acoustic Radiation Force - Ciancia, Sabrina; Cafarelli, Andrea; Zahoranova, Anna; Menciassi, Arianna; Ricotti, Leonardo (Frontiers in Bioengineering and Biotechnology, 2020)
Since biological systems exhibit a circadian rhythm (24-hour cycle), they are extremely sensitive to the timing of drug administration. Indeed, several disorders require a therapy that is synchronized with the onset of symptoms. A targeted therapy with spatially and temporally precise controlled drug release can guarantee a considerable gain in terms of efficacy and safety of the treatment compared to traditional pharmacological methods, especially for chronotherapeutic disorders. This paper presents a proof of concept of an innovative pulsatile drug delivery system remotely triggered by the acoustic radiation force of ultrasound. The device consists of a case, in which a drug-loaded gel can be embedded, and a sliding top that can be moved on demand by the application of an acoustic stimulus, thus enabling the drug release. Results demonstrate for the first time that ultrasound acoustic radiation force (up to 0.1 N) can be used for an efficient pulsatile drug delivery (up to 20 µg of drug released for each shot).